Capacitor electrode, method for producing same, and capacitor
By using short carbon fibers and carbon particles to form a three-dimensional structure between graphene sheets, the issue of increased resistance in graphene-based electrodes is resolved, resulting in a capacitor with high capacity and low resistance.
Patent Information
- Application Number
- JP2022201700
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2039-03-27
AI Technical Summary
The use of common carbon nanotubes (CNTs) in graphene-based electrodes inhibits ion diffusion between graphene sheets, leading to increased resistance at low temperatures due to improper control of the distance between graphene sheets.
Incorporating short carbon fibers with an average length of 10 μm or less and/or carbon particles with an average diameter of 0.1 μm or less between graphene sheets, forming a three-dimensional structure to enhance ion diffusibility and suppress sheet overlap.
This approach results in a capacitor electrode with high capacity and low resistance, even at low temperatures, by effectively utilizing the surface area of graphene and maintaining ion diffusion.
Smart Images

Figure 0007617531000002 
Figure 0007617531000003 
Figure 0007617531000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a capacitor electrode, a method for producing the same, and a capacitor. [Background technology]
[0002] Graphene has a theoretical specific surface area of approximately 2600 m 2 / g and is conductive, making it a promising electrode material for capacitors. However, if the distance between the graphene sheets is not properly controlled, the flat graphene sheets will overlap too much, and the surface area of the graphene cannot be fully utilized.
[0003] Patent Document 1 proposes the use of a graphene sheet assembly film in which a plurality of graphene sheet laminates, each of which has two or more graphene sheets laminated via a first carbon nanotube, are electrically and mechanically three-dimensionally connected to each other via a second carbon nanotube. It also proposes the use of single-walled carbon nanotubes having a length of 5 to 20 μm as the first and second carbon nanotubes. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2012 / 073998 Brochure Summary of the Invention [Problem to be solved by the invention]
[0005] However, when using conventional carbon nanotubes (CNTs), the basal planes of the CNTs interposed between the graphene sheets inhibit ion diffusion between the graphene sheets, which tends to increase resistance at low temperatures. [Means for solving the problem]
[0006] One aspect of the present invention relates to a capacitor electrode comprising a first carbon and a second carbon other than the first carbon, the first carbon comprising graphene, the second carbon being short carbon fibers having an average length of 10 μm or less and / or carbon particles having an average diameter of 0.1 μm or less, and the graphenes being stacked together with the second carbon interposed therebetween.
[0007] Another aspect of the present invention relates to a capacitor including the above-mentioned capacitor electrode.
[0008] Yet another aspect of the present invention relates to a method for manufacturing an electrode for a capacitor, comprising the steps of preparing an aqueous dispersion containing graphene oxide as a first carbon raw material and a second carbon, and reducing the graphene oxide in the aqueous dispersion, wherein the second carbon is short carbon fibers having an average length of 10 μm or less and / or carbon particles having an average diameter of 0.1 μm or less. Effect of the Invention
[0009] According to the present invention, a capacitor electrode having high capacity and low resistance even at low temperatures can be obtained by using graphene. [Brief description of the drawings]
[0010] [Figure 1] 1 is a partially cutaway perspective view of an electric double layer capacitor according to the present invention. [Figure 2A] 1 is a transmission electron microscope (TEM) photograph of the xerogel obtained in Example 1. [Figure 2B] FIG. 2B is an enlarged TEM photograph of a portion of FIG. 2A. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of highly crystalline graphene used in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The capacitor electrode according to this embodiment includes a first carbon and a second carbon other than the first carbon, the first carbon includes graphene, and the second carbon is short carbon fibers having an average length of 10 μm or less and / or carbon particles having an average diameter of 0.1 μm or less. The graphenes are stacked with the second carbon interposed therebetween. Thus, the ion diffusion between the graphenes is greatly improved, and a capacitor electrode having low resistance is obtained. In addition, the second carbon is interposed between the graphenes, so that the overlap between the graphene sheets is suppressed, and the surface area of the graphene can be more effectively utilized. On the other hand, when the second carbon is short carbon fibers and / or carbon particles, the ion diffusion between the graphenes is not hindered, unlike the case of using general CNTs.
[0012] Here, graphene is a carbon material whose minimum unit is a graphene sheet having a thickness of one carbon atom, and usually constitutes a laminate in which a plurality of graphene sheets are laminated. Also, a graphene sheet is an aggregate or molecule composed of sp2 bonded carbon having a thickness of one carbon atom, and has a honeycomb lattice structure that spreads in a sheet shape. Although general graphene usually has a flat sheet shape, here, graphene sheet laminates of various shapes having a disordered layer structure (or a disordered interlayer distance) are also included in the category of graphene. Graphene may partially contain a graphene analog such as graphene oxide. Hereinafter, graphene is also referred to as a graphene sheet laminate.
[0013] The capacitor electrode has, for example, a metal current collector and an electrode layer supported on the current collector, and the first carbon and the second carbon are contained in the electrode layer as active materials that adsorb and desorb ions.
[0014] (a) First carbon Graphene may have a microscopic three-dimensional structure (i.e., a fine structure). By having a three-dimensional structure, overlapping of graphene sheets is significantly suppressed, and the surface area of graphene can be more effectively utilized. A plurality of raised portions or a plurality of depressed portions are formed on the main surface of the graphene sheet laminate having a three-dimensional structure. By such a three-dimensional structure, the distance between the graphene sheets is appropriately controlled, and overlapping of the graphene sheets is effectively reduced.
[0015] The average number of layers of the graphene sheet laminate in graphene is, for example, 10 layers or less, and may be 5 layers or less. It is preferable that the graphene is closer to the minimum unit of graphene sheet (i.e., single-layer sheet) having a thickness of one carbon atom. The average number of layers may be the number of layers estimated from the interplanar distance (d002) calculated from the diffraction peak belonging to the 002 plane of the X-ray diffraction profile (for example, Abstracts of the 2015 Autumn Meeting of the Physical Society of Japan, p. 1014). Alternatively, it may be an estimated value obtained from an electron microscope (SEM, etc.) photograph of graphene. For example, the number of layers of graphene sheets can be estimated from the scale of the SEM photograph of graphene and the interplanar distance of the 002 plane (hereinafter also referred to as the basal plane) of the graphene sheet. For example, 20 arbitrary graphene sheet laminates are selected, the number of layers of each is estimated, the maximum value and the minimum value are omitted, and the average value of the middle 10 values is taken as the average number of layers.
[0016] The interlayer distance between graphene sheets in graphene (i.e., the distance between basal planes) may vary randomly. A random variation in the interlayer distance means that the graphene has low crystallinity. The greater the disorder in the graphene stacking structure, the more significant the variation in the interlayer distance becomes.
[0017] Graphene may have a three-dimensional structure, for example, a crimped structure or a folded structure. In this case, each graphene sheet laminate has a microporous structure. This allows ions to diffuse easily near the surface of the graphene. The presence of the curled or folded structure can be confirmed by electron microscope (SEM, TEM, etc.) photographs of graphene.
[0018] The crimped structure may be, for example, a structure having a plurality of randomly formed fold-like raised portions and recessed portions. The folded structure is a structure having a folded portion in which one graphene sheet laminate is partially folded a plurality of times, and is included in the category of the crimped structure. The height of the raised portion or the depth of the recessed portion formed in the folded portion may be greater than the thickness of the carbon portion of the graphene sheet laminate having that structure, and may be at least twice the thickness of the carbon portion.
[0019] The X-ray diffraction profile of the first carbon usually has a diffraction peak P1 assigned to the 002 plane. The greater the overlap between the graphene sheets and the higher the crystallinity of the graphene, the sharper the diffraction peak P1 becomes.
[0020] On the other hand, when graphene has a three-dimensional structure, the diffraction peak P1 becomes broad and can be separated into multiple peaks. A halo pattern attributed to an amorphous phase may be observed on the higher angle side of the diffraction peak P1 in the X-ray diffraction profile of the first carbon.
[0021] The interplanar distance (d002) of the 002 plane of the first carbon calculated from the X-ray diffraction profile may be, for example, 0.338 nm (3.38 Å) or more. d002 is calculated by performing waveform separation on the diffraction peak observed in the region around 2θ=26.38°, calculating d002 for each component, and calculating the average. The distance (d002) of the 002 plane of the first carbon is preferably 0.340 nm (3.40 Å) or more, more preferably 0.360 nm (3.60 Å) or more, and even more preferably 0.370 nm (3.70 Å) or more.
[0022] (b) Second Carbon The second carbon may be short carbon fibers having an average length of 10 μm or less and / or carbon particles having an average diameter of 0.1 μm or less.
[0023] (i) Short carbon fibers The short carbon fibers may be, for example, vapor-grown carbon fibers, carbon nanotubes, carbon nanofibers, etc. The short carbon fibers may have a hollow space (hollow portion) therein.
[0024] The average length of the short carbon fibers may be 10 μm or less, but from the viewpoint of increasing the ion diffusion between graphenes, 2 μm or less is preferable, and 0.1 μm or less is more preferable. The average length of the short carbon fibers can be analyzed from an electron microscope (SEM, TEM, etc.) photograph. For example, 20 short carbon fibers are arbitrarily selected, the length of each is measured, the maximum value and the minimum value are excluded, and the average value of the middle 10 values is taken as the average length. Since the short carbon fibers are short, 10 μm or less, they can be approximated to a straight line. Therefore, the length of the short carbon fibers means the length of the straight line when both ends of the short carbon fibers are connected with a straight line.
[0025] The average diameter of the short carbon fibers is, for example, 200 nm or less, and may be 5 nm or more and 200 nm or less, or 10 nm or more and 170 nm or less. The diameter of the short carbon fibers is the maximum length in the direction perpendicular to the length direction of the short carbon fibers, and the average diameter can be analyzed from an electron microscope (SEM, TEM, etc.) photograph. For example, 20 short carbon fibers are arbitrarily selected, and Each diameter is measured, the top five diameters from the maximum and the top five diameters from the minimum are discarded, and the average of the middle ten diameters is taken as the average diameter.
[0026] (ii) Carbon particles The average diameter of the carbon particles may be 0.1 μm or less, but from the viewpoint of increasing the ion diffusion between graphenes, it is preferable that it is 0.05 μm or less, and more preferable that it is 0.03 μm or less. The average diameter of the carbon particles can be analyzed from an electron microscope (SEM, TEM, etc.) photograph. For example, 20 arbitrary carbon particles are selected, the maximum diameter of each is measured, the maximum value and the minimum value are excluded, and the average value of the intermediate 10 values is taken as the average diameter. In addition, when the carbon particles can be separated, they can be measured by a laser diffraction type particle size distribution measuring device. In this case, the median diameter at 50% of the cumulative volume in the volume-based particle size distribution can be taken as the average diameter.
[0027] Specific examples of carbon particles include graphite, non-graphitizable carbon, graphitizable carbon, carbon black, etc. Among them, carbon black is preferable, and for example, acetylene black, ketjen black, thermal black, furnace black, channel black, etc. may be used. Note that a plurality of carbon particles (here, primary particles) may be linked to form a chain structure (secondary particles). In this case, the average diameter is the average diameter of the primary particles. The length of the chain structure is not particularly limited, but is preferably 2 μm or less, more preferably 0.5 μm or less, and more preferably 0.05 μm or less.
[0028] (iii) First carbon / second carbon ratio The ratio of the first carbon to the total of the first carbon and the second carbon may be 40 to 98 mass %, or may be 80 to 98 mass %. In order to obtain a capacitor electrode with a high capacity, it is desirable to have a large ratio of graphene having a large surface area. On the other hand, if the ratio of the first carbon is too large, the amount of the second carbon interposed between the graphene is reduced, and the effect of suppressing the overlapping of the graphene sheets is reduced. If the ratio of the first carbon is within the above range, the overlapping of the graphene sheets is significantly suppressed, and the capacity of the capacitor electrode can be efficiently increased.
[0029] (c) Binder The capacitor electrode may contain a binder. The binder has a role of supporting the bonding between the first carbons, between the second carbons, or between the first carbon and the second carbon when the mixture of the first carbon and the second carbon is formed into a sheet-like or film-like electrode layer. The binder also has a role of supporting the bonding between the electrode layer and the current collector.
[0030] Examples of binders that can be used include fluororesins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), and vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP); and water-soluble resins such as carboxymethyl cellulose (CMC), polyethylene oxide (PEO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylic acid (PAA), and polyvinyl acetate.
[0031] (d) Third component The electrode layer may contain other active materials such as activated carbon in addition to the first carbon and the second carbon. In addition, the present invention does not exclude the case where the electrode layer contains CNTs having an average length of more than 10 μm, and the electrode layer may contain a small amount of CNTs.
[0032] (e) Current collector The current collector may be a metal foil, a metal porous body, or the like. The current collector may be made of aluminum, copper, nickel, iron, stainless steel, platinum, or the like. An alloy containing these metals as a main component may also be used. The metal foil may be a plain foil, or may be a foil that has been roughened by etching or the like, or a foil that has been subjected to plasma treatment. The metal porous body may have, for example, a three-dimensional mesh structure.
[0033] The mass per unit area of the metal porous body is, for example, 500 g / m 2 Less than 150g / m 2 The porosity of the metal porous body may be, for example, 80 volume % to 98 volume %, and may be 90 volume % to 98 volume %.
[0034] The average pore size of the pores in the metal porous body may be, for example, 50 μm or more and 1000 μm or less, or may be 400 μm or more and 900 μm or less, or 450 μm or more and 850 μm or less.
[0035] Next, an example of a method for manufacturing a capacitor electrode will be described. (i) Dispersion liquid preparation process First, an aqueous dispersion containing a first carbon raw material and a second carbon is prepared. The first carbon raw material is a precursor of the first carbon, and graphene oxide is used here. The second carbon is short carbon fibers with an average length of 10 μm or less and / or carbon particles with an average diameter of 0.1 μm or less.
[0036] The aqueous dispersion may contain a dispersant such as carboxymethyl cellulose (CMC) in addition to the first carbon raw material, the second carbon, and water.
[0037] Graphene oxide is a graphene analogue having an oxygen-containing functional group, and is a material exfoliated from graphite in a single layer or multiple layers via oxidation of the graphite. The oxygen-containing functional group is a hydrophilic group such as a hydroxyl group, a carbonyl group, or a carboxyl group, and has water dispersibility.
[0038] The oxidation of graphite can be carried out, for example, using an oxidizing agent in water. Examples of the oxidizing agent that can be used include sulfuric acid, potassium permanganate, chromic acid, sodium dichromate, sodium nitrate, peroxide, persulfate, and organic peracid. A water-soluble solvent may be added to the water. Examples of the water-soluble solvent include alcohols, ketones such as acetone, and ethers such as dioxane and tetrahydrofuran. An aqueous dispersion of graphene oxide is produced by an oxidation reaction in water. An aqueous dispersion containing the first carbon raw material and the second carbon is obtained by adding the second carbon to the aqueous dispersion of graphene oxide.
[0039] The degree of oxidation (oxygen content) of graphene oxide may be, for example, 10 to 60 mass%, may be 20 to 50 mass%, or may be 30 to 50 mass%. The degree of oxidation of graphene oxide may be measured, for example, by X-ray photoelectron spectroscopy (XPS). The masses of carbon (C) and oxygen (O) contained in graphene oxide may be measured by XPS, and the mass ratio of oxygen to the total mass of carbon and oxygen may be calculated.
[0040] (ii) Reduction step Next, the graphene oxide is reduced in an aqueous dispersion containing the graphene oxide (first carbon raw material) and the second carbon, i.e., in the presence of the second carbon. The reduction method is not particularly limited, but may be, for example, hydrothermal treatment. For example, the aqueous dispersion may be sealed in an autoclave and subjected to hydrothermal treatment to generate a gel-like product. The temperature of the hydrothermal treatment may be, for example, 150°C or higher, preferably 170°C or higher and 200°C or lower.
[0041] In the hydrothermal treatment, a crosslinked structure between the first carbon and the second carbon can be generated. For example, the first carbon and the second carbon are crosslinked via a functional group such as an ether bond (-O-). By such hydrothermal treatment, a gel-like product containing graphene composited with the second carbon and having a three-dimensional structure can be obtained.
[0042] In order to further promote the reduction, the gel product may be contacted with a reducing agent. Examples of the reducing agent include metal hydrides, borohydrides, boranes, hydrazines or hydrazides, ascorbic acids, thioglycolic acids, cysteines, sulfurous acids, thiosulfates, and dithionous acids. For example, the gel product may be immersed in an aqueous solution containing a water-soluble reducing agent such as sodium ascorbate. The temperature of the aqueous solution may be, for example, 20 to 110°C, or may be 40 to 100°C, or may be 50 to 100°C. The amount of the reducing agent used may be appropriately adjusted depending on the type of reducing agent, the oxidation degree of graphene oxide, the amount of the gel product, and the like. The oxidation degree of graphene after reduction may be, for example, 40% by mass or less, or may be 20% by mass or less.
[0043] (iii) Freeze-drying process The gel product is then preferably freeze-dried. Freeze-drying can provide a dry gel (xerogel) in which the three-dimensional structure of graphene is highly maintained. Freeze-drying can be performed, for example, at -50°C to 0°C, preferably -50°C to -20°C, under reduced pressure of 100 Pa or less, and further 1 Pa or less.
[0044] Xerogel is a composite of graphene with a three-dimensional structure and a second carbon. The composite contains graphene with a three-dimensional structure stacked through the second carbon. The composite is used as an active material for electrodes for capacitors that exhibit high capacitance.
[0045] (iv) Electrode process Next, the composite of the first carbon and the second carbon is dispersed in a dispersion medium such as water together with a binder to prepare a slurry. At this time, if the second carbon is interposed between the graphene, rearrangement of the graphene sheets is suppressed even in the slurry, and further overlapping of the graphene sheets is suppressed. In addition, in the composite obtained through the hydrothermal treatment, the first carbon and the second carbon are usually crosslinked via a functional group, and the degree of freedom of movement of the graphene is limited. Therefore, the three-dimensional structure is easily maintained even in the slurry.
[0046] The obtained slurry is applied to a current collector and the coating is dried to form an electrode layer supported on the current collector, thereby obtaining a capacitor electrode. The electrode layer may then be rolled.
[0047] Next, an example of a capacitor including the above-mentioned capacitor electrode will be described. The above-mentioned capacitor electrode can be used as an electrode for, for example, an electric double layer capacitor, a lithium ion capacitor, or the like.
[0048] FIG. 1 is a partially cutaway perspective view of an electric double layer capacitor 10. As shown in FIG. The electric double layer capacitor 10 in the illustrated example includes a wound type capacitor element 1. The capacitor element 1 is configured by winding a first electrode 2 and a second electrode 3, each of which is in the form of a sheet, with a separator 4 interposed therebetween. The first electrode 2 and the second electrode 3 each have a first current collector and a second current collector made of metal, respectively, and a first electrode layer and a second electrode layer carried on the surface thereof, and exhibit capacitance by adsorbing and desorbing ions. For example, aluminum foil is used for the first and second current collectors. The surface of the current collector may be roughened by a method such as etching. For example, a nonwoven fabric containing cellulose as a main component is used for the separator 4. Lead wires 5a and 5b are connected to the first electrode 2 and the second electrode 3, respectively, as lead members. The capacitor element 1 is accommodated in a cylindrical exterior case 6 together with an electrolyte (not shown). The exterior The material of the case 6 may be, for example, a metal such as aluminum, stainless steel, copper, iron, or brass. The opening of the exterior case 6 is sealed with a sealing member 7. The lead wires 5a and 5b are led out to the outside so as to pass through the sealing member 7. The sealing member 7 is made of, for example, a rubber material such as butyl rubber.
[0049] The electrode layer contains an active material as an essential component, and may contain a binder, a conductive assistant, and the like as optional components. The active material contains the first carbon and the second carbon having the characteristics already described. The electrode layer is obtained, for example, by applying a slurry obtained by kneading the active material, a binder (e.g., carboxymethyl cellulose (CMC)), and the like together with water in a kneader to the surface of a current collector, drying the coating, and rolling it.
[0050] The electrolyte may be a mixture of a solvent and an ionic substance (e.g., an organic salt) dissolved in the solvent. The solvent may be a non-aqueous solvent or an ionic liquid. The concentration of the ionic substance in the electrolyte may be, for example, 0.5 to 2.0 mol / L.
[0051] The non-aqueous solvent is preferably a high boiling point solvent, for example, lactones such as γ-butyrolactone, carbonates such as propylene carbonate, polyhydric alcohols such as ethylene glycol and propylene glycol, cyclic sulfones such as sulfolane, amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, and formaldehyde can be used.
[0052] An organic salt is a salt in which at least one of the anion and the cation contains an organic substance. An example of an organic salt in which the cation contains an organic substance is a quaternary ammonium salt. An example of an organic salt in which the anion (or both ions) contains an organic substance is trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, mono-1,3-dimethyl-2-ethylimidazolinium phthalate, etc.
[0053] From the viewpoint of improving the voltage resistance characteristic, the anion preferably contains a fluorine atom, for example, BF4 - and / or PF6 - Preferred organic salts include, in particular, tetraalkylammonium salts such as ethyltrimethylammonium tetrafluoroborate.
[0054] In the above embodiment, a wound type capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention may also be applied to capacitors of other structures, such as stacked type or coin type capacitors.
[0055] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.
[0056] Example 1 In this example, a wound type electric double layer capacitor (Φ18 mm×L (length) 70 mm) was produced with a rated voltage of 2.8 V. A specific method for producing the electric double layer capacitor will be described below.
[0057] (i) Preparation of active material The second carbon, carbon black (acetylene black (average primary particle diameter 35 nm) manufactured by Denka Corp.), was added to an aqueous dispersion containing 0.35 mass% of graphene oxide, the first carbon raw material, and mixed in a thin film swirling high-speed mixer (Filmix, manufactured by Primix Corp.). (registered trademark) to prepare an aqueous dispersion having a total content of the first carbon raw material and the second carbon raw material of 0.39 mass %.
[0058] Next, the aqueous dispersion was hydrothermally treated at 180°C for 1 hour to obtain a gelled product. The gelled product was then immersed in a reducing agent, sodium ascorbate aqueous solution (sodium ascorbate concentration 1.0 mol / L), heated to 100°C and held for 2 hours to sufficiently reduce the graphene oxide. The gelled product was then freeze-dried at -20°C under reduced pressure of 100 Pa to obtain a xerogel.
[0059] Next, the xerogel (i.e., a composite of the first carbon and the second carbon) was dispersed in water together with CMC, which was a binder, to prepare a slurry. The amount of CMC used was 10 parts by mass per 100 parts by mass of the xerogel. The obtained slurry was applied to a current collector made of an Al foil with a thickness of 30 μm, and the coating was vacuum dried at 110° C. and rolled to form an electrode layer, thereby obtaining an electrode for a capacitor.
[0060] A pair of electrodes was prepared, a lead wire was connected to each of them, and the electrodes were wound with a separator made of cellulose nonwoven fabric to form a capacitor element, which was then housed in a specified exterior case together with an electrolyte and sealed with a sealing material to complete the electric double layer capacitor A1. The electrolyte used was a solution in which ethyl dimethyl imidazolium tetrafluoroborate was dissolved in propylene carbonate, a nonaqueous solvent, at a concentration of 1.0 mol / L. After that, the capacitor was aged at 60°C for 16 hours while applying the rated voltage.
[0061] [evaluation] Figure 2A shows a TEM image of the xerogel used in the preparation of the slurry in this example. Figure 2B shows an enlarged TEM image of a portion of Figure 2A. These images confirm that chain-like connections of primary particles of carbon black are present between multiple graphene sheet laminates.
[0062] The TEM images show a crinkled or folded structure with randomly formed fold-like protuberances and depressions. The height of the protuberances or the depth of the depressions formed in the folds are significantly greater than the thickness of the carbon part, and are at least twice the thickness of the carbon part.
[0063] In addition, when the xerogel was subjected to X-ray diffraction measurement, a broad halo pattern was observed at higher angles than the diffraction peak P1 assigned to the 002 plane, which is assigned to an amorphous phase, indicating the presence of a crimped or folded structure. The obtained X-ray diffraction profile was analyzed to determine the d002 of graphene, which was confirmed to be approximately 0.34 nm or more.
[0064] Next, the capacitance of the electric double layer capacitor A1 was determined at 25° C. and -30° C. In addition, the ratio of the capacitance at -30° C. to the capacitance at 25° C. (C(-30 / 20)) was determined. Since ion diffusion is rate-limiting at low temperatures, it can be said that the larger the C(-30 / 20) ratio, the lower the resistance to ion diffusion.
[0065] Comparative Example 1 A xerogel was prepared in the same manner as in Example 1, except that acetylene black, which was the second carbon, was not used. An electric double layer capacitor B1 was produced using the xerogel, and was similarly evaluated.
[0066] Comparative Example 2 The same as in Example 1, except that the second carbon, acetylene black, was not used. A xerogel was prepared, and an electric double layer capacitor B2 was produced in the same manner as in Example 1, except that 10 parts by mass of acetylene black per 100 parts by mass of the xerogel was added to the slurry, and was evaluated in the same manner.
[0067] Comparative Example 3 Except for using highly crystalline graphene instead of xerogel, a slurry containing acetylene black was prepared in the same manner as in Comparative Example 2, and an electric double layer capacitor B3 was produced and evaluated in the same manner as in Example 1. Fig. 3 shows an electron microscope (SEM) photograph of the highly crystalline graphene according to this comparative example.
[0068] The evaluation results of the above examples and comparative examples are shown in Table 1.
[0069] [Table 1]
[0070] Table 1 shows that the capacitance of the capacitor A1 is significantly higher than those of the capacitors B1 to B3, and that the capacitor A1 is a low-resistance capacitor with excellent ion diffusion even at low temperatures. The capacitance of the capacitors B1 and B2 is significantly lower than that of the capacitor A1, and the capacitances are almost the same. From this, it can be said that even if the xerogel and acetylene black are mixed during the preparation of the slurry, it is difficult to form a structure favorable for ion diffusion in which the graphenes are stacked with the acetylene black interposed therebetween, and it is also difficult to maintain the three-dimensional structure of the graphene. On the other hand, in the xerogel obtained by reducing an aqueous dispersion of graphene oxide and the second carbon (carbon black) and then freeze-drying it, the graphenes are stacked with the acetylene black interposed therebetween, and the three-dimensional structure of the graphene is considered to be maintained. This is considered to be due to the fact that the first carbon and the second carbon are cross-linked through a chemical bond such as an ether bond. [Industrial Applicability]
[0071] According to the present invention, an electric double layer capacitor having a high capacity and a low resistance even at low temperatures can be obtained. [Explanation of symbols]
[0072] 1: capacitor element, 2: first electrode, 3: second electrode, 4: separator, 5a: first lead wire, 5b: second lead wire, 6: exterior case, 7: sealing member, 10: capacitor
Claims
1. A first carbon, which is graphene; The second carbon is short carbon fibers or carbon particles, The X-ray diffraction profile of the first carbon has a diffraction peak P1 assigned to a 002 plane, and has a halo pattern assigned to an amorphous phase on the higher angle side than the diffraction peak P1, the interplanar distance of the 002 plane of the first carbon calculated from the X-ray diffraction profile is 0.360 nm or more; The graphenes are stacked together via the second carbon. Electrode for capacitor.
2. 2. The capacitor electrode according to claim 1, wherein the short carbon fibers are vapor-grown carbon fibers or carbon nanofibers.
3. 2. The capacitor electrode according to claim 1, wherein the carbon particles are selected from the group consisting of graphite, non-graphitizable carbon, graphitizable carbon and carbon black.
4. 4. The capacitor electrode according to claim 1, wherein the chain-like linked carbon particles are interposed between layers of the graphene laminate.
5. 5. The capacitor electrode according to claim 1, wherein a ratio of said first carbon to a total of said first carbon and said second carbon is 40 to 98 mass %.
6. 6. The capacitor electrode according to claim 1, further comprising a bridge structure between the first carbon and the second carbon.
7. The electrode for a capacitor according to any one of claims 1 to 6, wherein the degree of oxidation of the graphene is 40 mass% or less.
8. The capacitor electrode according to claim 1 , wherein the graphene has a three-dimensional structure.
9. The capacitor electrode according to any one of claims 1 to 8, wherein an average number of stacked graphene sheets in the graphene is 10 or less.
10. The capacitor electrode according to any one of claims 1 to 9, wherein an interlayer distance between graphene sheets in the graphene changes randomly.
11. The capacitor electrode according to any one of claims 1 to 10, wherein the graphene has a curled structure or a folded structure.
12. A capacitor comprising the capacitor electrode according to any one of claims 1 to 11.
Citation Information
Patent Citations
Energy storage device
JP2010205695A
Electrode for electricity storage device, electricity storage device, and method for manufacturing electrode for electricity storage device
JP2014225508A
Method for preparing hydrothermally prepared graphene / CNT composite aerogel, hydrothermally prepared graphene / CNT composite aerogel, and electrode for separation and detection of UA, da, and aa
JP2015078096A
Graphene sheet film linked with carbon nanotubes, method for producing same and graphene sheet capacitor using same
WO2012073998A1
Linked stacks of partly reduced graphene, process for producing linked stacks of partly reduced graphene, powder comprising linked stacks of partly reduced graphene, film comprising linked stacks of partly reduced graphene, graphene electrode film, process for producing graphene electrode film, and graphene capacitor
WO2014038600A1